Similar Supine Heart Rate Variability Changes During 24-h Exposure to Normobaric vs. Hypobaric Hypoxia - Tanner, Valérian; Faiss, Raphael; Saugy, Jonas; Bourdillon, Nicolas; Schmitt, Laurent; Millet, Grégoire P. (Frontiers in Neuroscience, 2021)
Purpose: This study aimed to investigate the differences between normobaric (NH) and hypobaric hypoxia (HH) on supine heart rate variability (HRV) during a 24-hour exposure. We hypothesized a greater decrease in parasympathetic-related parameters in HH than in NH. Methods: A pooling of original data from forty-one healthy lowland trained men was analyzed. They were exposed to altitude either in NH (FIO2 = 15.7 ± 2.0%; PB = 698 ± 25 mmHg) or HH (FIO2 = 20.9%; PB = 534 ± 42 mmHg) in a randomized order. Pulse oximeter oxygen saturation (SpO2), heart rate (HR), and supine HRV were measured during a 7-min rest period three times: before (in normobaric normoxia, NN), after 12 (H12), and 24 hours (H24) of either NH or HH exposure. HRV parameters were analyzed for time- and frequency-domains. Results: SpO2 was lower in both hypoxic conditions than in NN and was higher in NH than HH at H24. Subjects showed similarly higher HR during both hypoxic conditions than in NN. No difference in HRV parameters was found between NH and HH at any time. The natural logarithm of root mean square of the successive differences (LnRMSSD) and the high frequency spectral power (HF), which reflect parasympathetic activity, decreased similarly in NH and HH when compared to NN. Conclusion: Despite SpO2 differences, changes in supine HRV parameters during 24-h exposure were similar between NH and HH conditions indicating a similar decrease in parasympathetic activity. Therefore, HRV can be analysed similarly in NH and HH conditions.